Formation and Turnover of NSF- and SNAP-containing “Fusion” Complexes Occur on Undocked, Clathrin-coated Vesicle–derived Membranes - Swanton, Eileithyia (The American Society for Cell Biology, 1998)
Specificity of vesicular transport is determined by pair-wise interaction between receptors (SNAP receptors or SNAREs) associated with a transport vesicle and its target membrane. Two additional factors, N-ethylmaleimide-sensitive fusion protein (NSF) and soluble NSF attachment protein (SNAP) are ubiquitous components of vesicular transport pathways. However, the precise role they play is not known. On the basis that NSF and SNAP can be recruited to preformed SNARE complexes, it has been proposed that NSF- and SNAP-containing complexes are formed after SNARE-dependent docking of transport vesicles. This would enable ATPase-dependent complex disassembly to be coupled directly to membrane fusion. Alternatively, binding and release of NSF/SNAP may occur before vesicle docking, and perhaps be involved in the activation of SNAREs. To gain more information about the point at which so-called 20S complexes form during the transport vesicle cycle, we have examined NSF/SNAP/SNARE complex turnover on clathrin-coated vesicle–derived membranes in situ. This has been achieved under conditions in which the extent of membrane docking can be precisely monitored. We demonstrate by UV-dependent cross-linking experiments, coupled to laser light-scattering analysis of membranes, that complexes containing NSF, SNAP, and SNAREs will form and dissociate on the surface of undocked transport vesicles.